Prevalence of Subclinical Thyroid Dysfunction and Its Relation to Socioeconomic Deprivation in the Elderly: A Community-Based Cross-Sectional Survey - Sue Wilson; Jim Parle; Lesley Roberts; Andrea Roalfe; Richard Hobbs; Penny Clark; Michael C. Sheppard; Michael D. Gammage; Helen Pattison; Jayne A. Franklyn (2006)
Population-based screening has been advocated for subclinical thyroid dysfunction in the elderly because the disorder is perceived to be common, and health benefits may be accrued by detection and treatment.The objective of the study was to determine the prevalence of subclinical thyroid dysfunction and unidentified overt thyroid dysfunction in an elderly population.A cross-sectional survey of a community sample of participants aged 65 yr and older registered with 20 family practices in the United Kingdom.Exclusions included current therapy for thyroid disease, thyroid surgery, or treatment within 12 months.Tests of thyroid function (TSH concentration and free T4 concentration in all, with measurement of free T3 in those with low TSH) were conducted. EXPLANATORY VARIABLES: These included all current medical diagnoses and drug therapies, age, gender, and socioeconomic deprivation (Index of Multiple Deprivation, 2004).Standardized prevalence rates were analyzed. Logistic regression modeling was used to determine factors associated with the presence of subclinical thyroid dysfunction.A total of 5960 attended for screening. Using biochemical definitions, 94.2% [95% confidence interval (CI) 93.8-94.6%] were euthyroid. Unidentified overt hyper- and hypothyroidism were uncommon (0.3, 0.4%, respectively). Subclinical hyperthyroidism and hypothyroidism were identified with similar frequency (2.1%, 95% CI 1.8-2.3%; 2.9%, 95% CI 2.6-3.1%, respectively). Subclinical thyroid dysfunction was more common in females (P < 0.001) and with increasing age (P < 0.001). After allowing for comorbidities, concurrent drug therapies, age, and gender, an association between subclinical hyperthyroidism and a composite measure of socioeconomic deprivation remained.Undiagnosed overt thyroid dysfunction is uncommon. The prevalence of subclinical thyroid dysfunction is 5%. We have, for the first time, identified an independent association between the prevalence of subclinical thyroid dysfunction and deprivation that cannot be explained solely by the greater burden of chronic disease and/or consequent drug therapies in the deprived population.